MELIC TRANSLATION - Szota, Weronika (Neofilolog, 2018)
In the following paper the author presents selected theories and approaches related to the translation of songs. She believes that these are crucial in understanding the melic translation process. Some aspects of the melic translation process itself, especially those connected with the translator’s decision, are also mentioned. They are described in order to show the need for an interdisciplinary perspective when approaching the topic. The main aim of the article is to present a possible solution for song translation with reference to the theories presented. The solution proposed involves the need to keep in mind not only ‘the message’ of the song, semantic dominant, harmonic dominant, and ‘the sound’ but also the fact that children are the main recipients.